Empowering Merdeka Play: Unleashing Potential Through Project-Based Learning in Kindergarten - Agusniatih, Andi; Nurhayati, Nurhayati; Durrotunnisa, Durrotunnisa (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research responds to the limitations of conventional learning methods and minimal educational game tools in stimulating children's interest in learning, this study explores the effectiveness of Project-Based Learning (PjBL) in the implementation of the Merdeka Play curriculum for early childhood education. The research, a descriptive qualitative study, involved 30 children aged 4-6 at Pembina Kindergartens. Through direct observation, interviews, and documentation, the study assessed the development of religious values (80%), self-identity (73%), and literacy/STEAM skills (75%) using the PjBL approach. The overall average achievement across these aspects was 76%. The findings indicating the effectiveness of PjBL, especially through independent play, in facilitating holistic development among young learners. This research contributes insights into enhancing early childhood education with implications for curriculum design and teaching methodologies.Â